1964
DOI: 10.1029/jz069i024p05427
|View full text |Cite
|
Sign up to set email alerts
|

The electric field of a New Mexico dust devil

Abstract: On August 21, 1962, a continuously recording inverted field mill, installed on an open semidesert area near the NMIMT campus, recorded the passage of a fairly large dust devil at a time when I was present to make visual observations. Its closest approach to the field mill was about 450 m, established by reference to power line poles and roads. The bulk of the visible dust cloud was contained roughly in a vertical cylinder estimated to have a diameter of 20 m and a height of 120 m. Experience acquired in observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 3 publications
7
75
0
Order By: Relevance
“…The time evolution of space charge density is very similar to the initial accumulation of the thunderstorm space charge in the QE heating model before a conventional breakdown is reached [Pasko et al, 1997]. This maximum electric field for a typical terrestrial dust devil is difficult to compare with experimental measurements, all of which have strongly saturated at a few kV/m [Freier, 1960;Crozier, 1964Crozier, , 1970Farrell et al, 2004], but the predicted value of 150 kV/m is not inconsistent with these measurements. Very recently, Jackson and Farrell (submitted man- Melnik and Parrot [1998], the dissipation of dust grain charge due to atmospheric conductivity is fully considered in our FE simulation.…”
Section: Quasi-electrostatic Dust Devil Simulationsmentioning
confidence: 74%
See 3 more Smart Citations
“…The time evolution of space charge density is very similar to the initial accumulation of the thunderstorm space charge in the QE heating model before a conventional breakdown is reached [Pasko et al, 1997]. This maximum electric field for a typical terrestrial dust devil is difficult to compare with experimental measurements, all of which have strongly saturated at a few kV/m [Freier, 1960;Crozier, 1964Crozier, , 1970Farrell et al, 2004], but the predicted value of 150 kV/m is not inconsistent with these measurements. Very recently, Jackson and Farrell (submitted man- Melnik and Parrot [1998], the dissipation of dust grain charge due to atmospheric conductivity is fully considered in our FE simulation.…”
Section: Quasi-electrostatic Dust Devil Simulationsmentioning
confidence: 74%
“…The height and diameter of this generator region can be specified arbitrarily and we assume that the generator region fills the entire dust devil. Although more complicated charge structures can be included in this model, the dipole model of a dust devil is thought to be reasonable and has been used to estimate space charge densities [Crozier, 1964;Farrell et al, 2004]. The dipole charge model has a uniform distribution of negative space charge density at the dust devil top and a uniform distribution of positive space charge density at the dust devil bottom in a modeled cylindrical dust cloud.…”
Section: Quasi-electrostatic Dust Devil Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Terrestrial dust devils provide some of the strongest indirect evidence for Martian dust devil electrification. Freier [1960] and Crozier [1964] found that modest terrestrial dust devils of $10-m diameter and $100-m height possess a substantial DC electric field on the order of 0.6 kV/m. These fields were consistent with the cloud possessing a macroscopic electric dipole moment, M, on the order of $1 C-m oriented toward the nadir.…”
Section: Evidence For Martian Dust Electrificationmentioning
confidence: 99%